Improvements in Care in Acute Pancreatitis by the Adoption of an Acute Pancreatitis Algorithm - Bragg, Jack D; Cox, Karen R; Despins, Laurel; Hall, Les W; Bechtold, Matthew L (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Mortality rate and length of stay for acute pancreatitis.